Penerapan Syarat Penulisan Berita Pada Rubik Politik Metropolitan.Id Dilihat Dari Kelengkapan Unsur 5W+1H Dan Penggunaan Narasumber - Muhamad Raihan Jamil; Widyastuti Widyastuti; Titiek Surya Ningsih (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
This study aims to find out the requirements for writing news in the political rubric at metropolitan.id in terms of the completeness of the 5W+1H elements and the use of sources. This type of research is classified as explanatory using a quantitative approach. The source of data from this study is through the online media metropolitan.id. Then data was collected by conducting a survey using research instruments and distributing coding sheets to 3 coders with 3 news. To find out the agreement between the 3 coders on the category with a reliability test. To find out the research results of the two variables using rotated sampling and get 7 news samples that must be analyzed. The results of analyzing news from the category of completeness of the 5W + 1H elements and the use of sources. Sample 1 the completeness of news elements is 100% and the use of expert sources is 100%, Sample 2 the completeness of news elements is 90% and the use of expert sources is 100%, Sample 3 the completeness of news elements is 88% and the use of expert sources is 100%, Sample 4 the completeness of news elements 100% and the use of expert sources is 100%, Sample 5 the completeness of news elements is 90% and the use of expert sources is 100%, Sample 6 the completeness of news elements is 92% and the use of expert sources is 100%, Sample 7 the completeness of news elements is 81% and the use expert sources 100%.